Evaluation of newly adapted clip marker system in ultrasound-guided core needle biopsy for suspicion of breast cancer - Schulz-Wendtland, Rüdiger; Dankerl, Peter; Dilbat, G.; Bani, Mayada; Fasching, Peter; Heusinger, K.; Lux, Michael P.; Löhberg, Christian; Jud, Sebastian; Rauh, Claudia; Bayer, Christian M.; Beckmann, Matthias; et al. (Geburtshilfe und Frauenheilkunde, 2013)
Introduction: A newly adapted clip system for intramammary marking during ultrasound-guided core needle biopsy for suspicion of breast cancer is described and evaluated here. Material and Method: Fifty patients with suspicion of breast cancer (cT2) had ultrasound-guided core needle biopsy using a newly adapted clip marker system (HistoCore™ and O-Twist Marker™). Subsequently, ultrasound follow-up and tomosynthesis scans were done to determine the location of the marker clips. Results: No dislocation of the marker clip was detected on ultrasound in 45 of 50 patients (90%), and 5 patients (10%) had a maximum dislocation of 5 mm along the x-, y- or z-axis. Tomosynthesis scans demonstrated precise placement without dislocation of the clip markers in 48 patients (96%); 2 patients (4%) had a maximum dislocation of 3 mm along the x-, y- or z-axis. Conclusion: The newly developed clip marker system, a combination of a single-use breast biopsy needle and a precise, length-adapted intramammary marker clip, represents a further improvement in oncological therapy. This is of particular importance for patients requiring subsequent neoadjuvant chemotherapy, as in cases with complete tumour remission, there is no target point for preoperative, ultrasound-guided wire marking. © Georg Thieme Verlag KG Stuttgart New York.
CRIS-Team Scopus Importer:2023-03-08
Keywords: biopsy; breast; breast cancer; ultrasound